Deeply responsible business : a global history of values-driven leadership - Jones, Geoffrey, 1952- (Cambridge, Massachusetts ; London, England : Harvard University Press, 2023)
"After years of maximizing profits, corporate social responsibility has entered the mainstream, but what does this really mean and what does it take to run a successful purpose-driven business? Harvard Business School's lead authority on socially responsible enterprises profiles fourteen business leaders, working across countries and in vastly different fields, from the nineteenth century to today, to showcase the challenges and upside to deeply responsible business"--
Includes bibliographical references and index.
GenEd
Keywords: Social responsibility of business -- History -- Case studies; Business ethics -- History -- Case studies; Leadership -- Moral and ethical aspects -- History -- Case studies; Organizational change -- History -- Case studies